1-2x=3x-11

Simple and best practice solution for 1-2x=3x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-2x=3x-11 equation:


Simplifying
1 + -2x = 3x + -11

Reorder the terms:
1 + -2x = -11 + 3x

Solving
1 + -2x = -11 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
1 + -2x + -3x = -11 + 3x + -3x

Combine like terms: -2x + -3x = -5x
1 + -5x = -11 + 3x + -3x

Combine like terms: 3x + -3x = 0
1 + -5x = -11 + 0
1 + -5x = -11

Add '-1' to each side of the equation.
1 + -1 + -5x = -11 + -1

Combine like terms: 1 + -1 = 0
0 + -5x = -11 + -1
-5x = -11 + -1

Combine like terms: -11 + -1 = -12
-5x = -12

Divide each side by '-5'.
x = 2.4

Simplifying
x = 2.4

See similar equations:

| x-3/8=1-x/3 | | 3m+5=25 | | (20a^2b)/(4a^2b2) | | x(x)+3x-10=-6 | | 3x-(5)=4 | | 2a-3=-17 | | 4x+6=5*2x | | 6-x=4(3x-5) | | 5x-88y=120 | | C=(3.14)(12) | | 7c+2=2+5c-5 | | -2(-2u-4)=4n+11 | | 35x+0.10y=25x+0.15y | | x^6-4x^5-45x^4=0 | | -6+-12-6= | | 3(c-12)=15 | | -8(t-4)-(t+6)=5 | | A-4+5a=-16 | | 4n-4=36 | | x^2-1x+.25=0 | | 14=w(3-2w) | | 11=n+11 | | -5c+10=35 | | 2h+3m+2x-3m= | | m-3/7 | | -2/3(5x-6)=1 | | 9x+9=9x-8 | | -0.4(40)+0.8x=0.4(40+x) | | 10x+11=11x+20 | | 6(7+3n)-7(-8n+1)=-39 | | 3858.25=1925+175.75x | | x-0.15x-9.00=42.00 |

Equations solver categories